Energy systems thinking and the decarbonization of heat in the UK - Malcolm Keay (The Oxford Institute for Energy Studies, 2020)
The UK Government's net-zero carbon objective has stimulated thinking about the technical options for decarbonizing heat. Less attention has been paid to the policy challenges the goal involves, and in particular the need for a system-wide approach to policy making. This would require a fundamental change in the Government's policy paradigm and the use of innovative policy instruments. So far, there is little sign that the Government has appreciated the scale of the policy challenge.
Keywords: 330; decarbonisation; EL 39; EL39; Energy Policy; energy systems; heat; UK